Dalla pantomima classica al Ballet d'action (Mantichora. Italian Journal of Performance Studies, 2020)
In the eighteenth century the neoclassical reflection on the artwork as an imitation of nature translates into the necessity of a radical reform for the choreutical art, which must recover a dramaturgical meaning. The practical model to follow for an imitative reconsideration of the dance is the ancient pantomime, the perfect example of the union between poetry, dance and music, aspiring to represent on scene a complete story and the emotions of the characters; the philosophical model which stands at the basis of the debate is the dialogical treatise on dance by Luciano di Samosata. The ancient reflection on the saltatio represents the start point for the neoclassical re-elaboration of the ballet d’action codified by Franz Anton Hilverding, Gasparo Angiolini and Jean-Georges Noverre.